Profesionalitas Nazir Wakaf: Studi Manajemen Wakaf Produktif di Lembaga Wakaf Daarut Tauhiid - Wildan Munawar (Universitas Pembangunan Nasional Veteran Jakarta, 2021)
AbstractNazir has a central role in management and development of waqf assets. A nazir’s method of managing waqf assets will decide the quality and quantity of the use of waqf assets, so that the existence of a professional work team will make the waqf assets more developed and productive. The purpose of this study was to determine the professionalism of waqf nazir by analyzing the management of productive waqf in the Daarut Tauhiid Bandung waqf institution. This research used a qualitative descriptive approach by analyzing productive waqf management from three aspects, namely nazir, waqf assets, and finance at the Daarut Tauhiid waqf institution. The data collection techniques are observation, interviews, documentation, and literature study. The data analysis technique used interactive model analysis by Miles and Huberman. The findings of this study indicate that productive waqf management at the Daarut Tauhiid Waqf Institution, which is reflected in three aspects, namely nazir, asset management, and financial reporting has gone well. This is supported by professional and competent nazirs in managing and developing waqf assets productively through collaboration with various parties; as well as management of waqf finances in a transparent and accountable manner through reporting to BWI, the community and waqif. AbstrakNazir memiliki peran sentral dalam pengelolaan dan pengembangan aset wakaf. Cara nazir dalam memperlakukan aset wakaf akan menentukan kualitas dan kuantitas pemanfaatan aset wakaf, sehingga keberadaan tim kerja yang profesional menjadikan aset wakaf akan semakin berkembang dan produktif. Tujuan penelitian ini untuk mengetahui profesionalitas nazir wakaf dengan menganalisa manajemen wakaf produktif di lembaga wakaf Daarut Tauhiid Bandung. Metode penelitian ini menggunakan pendekatan deskriptif kualitatif dengan menganalisa manajemen wakaf produktif dari tiga aspek, yaitu nazir, aset wakaf, dan keuangan di lembaga wakaf Daarut Tauhiid. Adapun teknik pengumpulan data menggunakan observasi, wawancara, dokumentasi dan studi kepustakaan. Teknik analisis data menggunakan analisis model interaktif Miles dan Huberman. Temuan penelitian ini menunjukkan bahwa manajemen wakaf produktif di Lembaga Wakaf Daarut Tauhiid yang direfleksikan melalui tiga aspek yaitu nazir, pengelolaan aset, dan pelaporan keuangan telah berjalan dengan baik. Hal ini didukung oleh para nazir yang profesional dan kompeten dalam mengelola dan mengembangkan aset wakaf secara produktif melalui kerja sama dengan berbagai pihak, dan juga pengelolaan keuangan wakaf secara transparan dan akuntabel melalui pelaporan kepada BWI, masyarakat dan waqif.